2021
DOI: 10.3389/feart.2021.762703
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Export From Two Contrasting Rural Watersheds in the (Sub) Humid Ethiopian Highlands

Abstract: Establishing worldwide sustainable and phosphorus efficient cropping systems is urgently needed because the supply of suitable phosphate rock is limited, and excess phosphorus in streams causes eutrophication. One of the impediments in the developing world for sustainable P practices is the lack of studies on P transport and its eventual disposition in the environment. One of these regions with few studies is the Ethiopian Highlands, with permeable volcanic soils. The objective was to establish baseline data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 88 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…A sampling date was not given in Tibebe et al (2019). Sishu et al (2021), similarly to Alemu et al (2017), observed for the Robit Bata watershed that drains to Lake Tana, the maximum dissolved TP concentrations in the rain phase was 3.4 mg DP/l. Baseflow concentrations during the dry phase were <0.1 mg DP/l.…”
Section: Introductionmentioning
confidence: 99%
“…A sampling date was not given in Tibebe et al (2019). Sishu et al (2021), similarly to Alemu et al (2017), observed for the Robit Bata watershed that drains to Lake Tana, the maximum dissolved TP concentrations in the rain phase was 3.4 mg DP/l. Baseflow concentrations during the dry phase were <0.1 mg DP/l.…”
Section: Introductionmentioning
confidence: 99%